The effects of distributed leadership on teaching innovation in Shanghai, China: the mediating roles of teacher autonomy, teacher collaboration, and teacher self-efficacy - Gong, Jing (Frontiers in Psychology, 2025)
IntroductionTeaching innovation (TI) is crucial with respect to efforts to cultivate innovative talent and enhance national competitiveness. To promote TI, the Chinese government has issued policy documents that have emphasized the need to overcome the traditional management model, which focuses on the “principal's individual heroism,” and to encourage schools to implement distributed leadership (DL) with the goal of achieving multiparty cogovernance. However, few studies have investigated whether and how the implementation of DL in the centralized and bureaucratic management models used in China can foster TI among teachers.MethodsTo address this gap, this study examines 3,976 teachers working at the lower secondary level in Shanghai, China, on the basis of data obtained from the 2018 Teaching and Learning International Survey (TALIS) dataset; in this context, a structural equation model (SEM) is used to compare a parallel mediation model constructed by reference to self-determination theory (SDT) with a chain mediation model constructed through the integration of SDT with conservation of resources theory (COR).ResultsThe results of this research reveal the superiority of the chain mediation model, according to which two independent mediation paths pertaining to teacher collaboration (TC) and teacher self- efficacy (TSE), as well as the two chain mediation paths of TC → TSE and teacher autonomy (TA) → TSE, are significant with respect to the relationship between DL and TI.DiscussionTheoretically, this study clarifies the mechanism underlying the influence of DL on TI in collectivist cultures; practically, it provides a reference for management practice for lower secondary school teachers with respect to TI.